Microgravity Oxygen Diffusion and Water Retention Measurements in Unsaturated Porous Media aboard the International Space Station. Issue 6 (16th June 2015) - Heinse, R.; Jones, S.B.; Or, D.; Podolskiy, I.; Topham, T.S.; Poritz, D.; Bingham, G.E.
Abstract : Water distribution patterns in pore spaces of particulate porous media directly control the resulting diffusion pathway for air required for biological activity (e.g., plant root respiration). Motivated by the potential of using plants for future life‐support systems in space, the question arises whether fluid behavior in porous media is significantly altered under microgravity (≈10 −6 g earth ) conditions. Altered fluid phase distribution has been suspected in the onset of hypoxia in plant root modules under microgravity, yet the exact mechanisms remain uncertain. The Optimization of Root Zone Substrates (ORZS) experiment was the first to directly measure porous‐media water retention and oxygen diffusion parameters under prolonged microgravity conditions (sufficient for equilibration of the fluid phases). Porous‐ceramic aggregates tested included 1‐ to 2‐mm Turface, 0.25‐ to 1‐mm Profile, and a 50:50 mixture of both. Each porous medium had three replicates in a nine‐cell array. The experiment used sealed dual‐chamber diffusion cells controlled by an automated measurement system with water‐content adjustment. Sensors measured matric potentials and water input or withdrawal in the media, along with oxygen concentrations dynamics in the gas‐filled chambers confining the medium. The effective oxygen‐diffusion coefficients were determined from temporal variations in measured oxygen‐concentrations fitted to a Fickian‐type relationship for the dual‐chamber geometry. Ground‐based determinations of matric potential and diffusion coefficients as a function of air‐filled porosity were compared to microgravity data. Results pointed to enhanced hysteresis in the oxygen‐diffusion dependency on bulk air‐filled porosity in microgravity indicative of altered water‐distribution patterns relative to Earth‐based measurements. During drying we observed fundamentally different diffusivities in Profile and Mix attributed to nonuniform water distributions forming under drying conditions dominated by capillary and viscous forces in the absence of a hydrostatic force not observed on Earth. Water‐retention parameters were not significantly different from Earth‐based parameters, although gas diffusion parameters were significantly different for finer particle‐sized media. The apparent reduction in the volume‐averaged diffusive transport in microgravity may require adjustment in plant‐growth system management protocols and model development for reliable response prediction of microgravity porous‐medium systems.